Differential levels of anti-Mycobacterium tuberculosis-specific IgAs in saliva of household contacts with latent tuberculosis infection - Ruiz-Tagle, Cinthya; Naves, Rodrigo; García, Patricia; Günther, Anna; Schneiderhan-Marra, Nicole; Balcells, María Elvira (Frontiers in Medicine, 2023)
Introduction: Mucosal immunity is strongly elicited in early stages of many respiratory and enteric infections; however, its role in tuberculosis pathogenesis has been scarcely explored. We aimed to investigate Mycobacterium tuberculosis (Mtb) specific IgA levels in saliva in different stages of latent Tuberculosis Infection (TBI). Methodology: A multiplex bead-based Luminex immunoassay was developed to detect specific IgA against 12 highly immunogenic Mtb antigens. A prospective cohort of household contacts (>14 years) of pulmonary TB cases was established in Santiago, Chile. Contacts were classified as Mtb-infected or not depending on serial interferon-γ release assay results. Saliva samples were collected and tested at baseline and at a 12-week follow-up. Results: Mtb-specific IgA was detectable at all visits in all participants (n=168), including the "non-Mtb infected" (n=64). Significantly higher median levels of IgA were found in the "Mtb infected" compared to the uninfected for anti-lipoarabinomannan (LAM) (110 vs 84.8 arbitrary units (AU), p<0.001), and anti-PstS1 (117 vs 83 AU, p<0.001), anti-cell membrane fraction (CMF) (140 vs 103 AU, p<0.001) and anti-Culture Filtrate Proteins (CFP) (median 125 vs 96 AU, p<0.001), respectively. Nonetheless, the discriminatory performance of these specific mucosal IgA for TBI diagnosis was low. Conclusion: Saliva holds Mtb-specific IgA against several antigens with increased levels for anti-LAM, anti-PstS1, anti-CMF and anti-CFP found in household contacts with an established TBI. The role of these mucosal antibodies in TB pathogenesis, and their kinetics in different stages of Mtb infection merits further